ACHIEVING SUSTAINABLE FOOD SECURITY IN EBONYI STATE THROUGH URBAN AGRICULTURE - OJIUZOR, P. E; NKAMA NNACHI AMA; OBOH, ENYINNAYA N; OZURUONYE M (International Studies Journal)
This study investigated achieving sustainable food security in Ebonyi State through urban agriculture. A descriptive survey design was adopted for the study. The population of the study was 300 urban farmers across the state, comprising of 150 males and 150females and this population formed the sample size for the study. Some concepts were clarified. A 3 in-1 instrument titled sustainable food security through urban agriculture (SFSTUAQ) was used for data collection. Three research questions and three hypotheses guided the study. The research questions were answered using mean rating t-test. The findings of the study revealed that there was a high level of awareness and participation among urban farmers due to encouragement from government. It was therefore recommended that co-opting urban farmers into co-operative societies will help immensely in reducing urban poverty.